2017
DOI: 10.1039/c6dt04129a
|View full text |Cite
|
Sign up to set email alerts
|

Molecular interactions between Geobacter sulfurreducens triheme cytochromes and the electron acceptor Fe(iii) citrate studied by NMR

Abstract: Proteomic and genetic studies have identified a family of five triheme cytochromes (PpcA-E) that are essential in the iron respiratory pathways of Geobacter sulfurreducens. These include the reduction of Fe(iii) soluble chelated forms or Fe(iii) oxides, which can be used as terminal acceptors by G. sulfurreducens. The relevance of these cytochromes in the respiratory pathways of soluble or insoluble forms of iron is quite distinct. In fact, while PpcD had a higher abundance in the Fe(iii) oxides supplanted G. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 45 publications
0
20
0
Order By: Relevance
“… Comparison of the most affected residues in the redox complexes established between PpcA from G. sulfurreducens and the elctron acceptors Fe-NTA (this work), Fe-citrate ( Ferreira et al, 2017 ) and AQ(H 2 )DS ( Dantas et al, 2014a , 2015 ). The residues highlighted in red and blue correspond to those that showed a decrease in the peak data height above 40% or a significant deviation in their chemical shift, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… Comparison of the most affected residues in the redox complexes established between PpcA from G. sulfurreducens and the elctron acceptors Fe-NTA (this work), Fe-citrate ( Ferreira et al, 2017 ) and AQ(H 2 )DS ( Dantas et al, 2014a , 2015 ). The residues highlighted in red and blue correspond to those that showed a decrease in the peak data height above 40% or a significant deviation in their chemical shift, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, previous studies have also shown that the heme IV region in the cytochrome PpcA from G. sulfurreducens was also involved in the formation of redox complexes with other electrons acceptors, namely the humic substance analog (AQDS) and Fe-citrate ( Dantas et al, 2014a , 2015 ; Ferreira et al, 2017 ). A comparison of the interacting polypeptide regions between PpcA and the three electron acceptors are summarized in Figure 7 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The heme midpoint potentials are found to lie within a rather narrow range, from the lowest of Heme I equal to −162 mV to the highest potential of Heme IV, around −133 mV. 26 Nuclear magnetic resonance (NMR) chemical shift perturbation measurements have demonstrated the presence of specific binding sites on the PpcA surface for small molecule redox substrates 27,28 and partner redox proteins. 29 Similarly, PpcA dimerization induced by anionic porphyrin binding also points toward an electrostatic surface that is mapped for recognition at a single surface location.…”
mentioning
confidence: 99%
“…Evidence for site-selective tuning of the heme cofactors in PpcA is seen by the heme methyl group proton NMR chemical shift patterns that are distinct, and readily distinguishable for each of the three heme cofactors. 27,28 The differing chemical shift patterns observed for the heme cofactors in both the cytochromes c 3 and c 7 families are significant since they provide a measure of the modulation of electron spin densities at atomic sites on the porphyrin ring which are found to be characteristically tuned for each heme cofactor. 31−35 A direct approach for characterization of site-specific electronic structure configuration of ferric hemes is through electron paramagnetic resonance (EPR) spectroscopy.…”
mentioning
confidence: 99%